A new extensional mixing element for improved dispersive mixing in twin-screw extrusion, part 2: experimental validation for immiscible polymer blends - Carson, Sidney O. (2018)
In Part 1 of this work, we presented a novel static extensional mixing element (EME) for twin-screw extrusion operations and validated the design in terms of the type of flow experienced by the melt upon dispersive mixing. In Part 2, we experimentally demonstrate the ability of the EME to yield improved dispersive mixing when compared with standard kneading-block-induced mixing for immiscible polypropylene/polystyrene blends of varying viscosity ratios between 0.3 and 10. The extensional flow characteristics of the EME improved the dispersion of polystyrene in the blends over all viscosity ratios, with improvements of 30% and above as measured by the cumulative area ratio measurements of polystyrene phases smaller than 1 μm2. The improvement in dispersive mixing seen from the EME for high viscosity ratio blends opens up applications in other areas, such as dispersion of nanoparticles or in reactive extrusion operations